Assessment of Knowledge, Perception, Attitude and Practice of Elevated Blood Pressure in Hypertensive Patients (Iraqi population) - Mohammed, Mohammed Mahmood (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2018)
Background: the patient’s perceptions about hypertension play an important role to reach the best control of this chronic disease. However, many hypertensive patients particularly the elderly present with uncontrolled blood pressure, which is a leading factor for mortality. Patient's knowledge and modifications of life style can contributes in the controlling of hypertension and preventing their long-term complications. Methods: Cross-sectional study, data from 212 hypertensive patients was collected from medical outpatient clinics in Baghdad along period of more than one year. Level of knowledge, attitude, perceptions and practice about hypertension were assessed using questionnaire sheet prepared for this purpose. Results: There were 212 hypertensive patients, 138 (65.1%) were women and 47 (34.9%) were men. Mean ± standard deviation age of patients was 56.56 ± 9.58 years. Most of the patients had completed high school (n = 179, 84.43%), and nearly half of them were have a job as average (n = 114, 53.8%). In general, more than half of participants revealed good knowledge, attitude and perception about elevated blood pressure, but unfortunately there are still a cogent percent of Iraqi patients present with poor knowledge and practice regarding to risk factors of hypertension, benefits of life style modifications mainly exercise, and taking healthy diet. Patient's knowledge, attitude, perception & practice were positively related to the educational level of hypertensive patients. Conclusion: This study demonstrated a non-convincing knowledge, attitude and perception and poor practice about hypertension in patients with elevated blood pressure in the study population. More efforts should be made to educate patients about the acquaintance of hypertension and the suitable individual way of treatment. Keywords: Hypertension, Patient’s knowledge, perception, attitude, practice.